ANALISIS DAMPAK PENGGUNAAN DANA DESA TERHADAP PEMBANGUNAN EKONOMI PEDESAAN DI KECAMATAN PANDAWAN KABUPATEN HULU SUNGAI TENGAH TAHUN 2016 - MUHAMMAD FAISAL NOFIAN (PPJP Universitas Lambung Mangkurat, 2018)
The research was conducted to (1) Analyze the impact of the impact of village funds on rural economic development in terms of income increase and poverty reduction in rural Pandawan District ; (2) To analyze the community’s view of the use of village funds for economic development and rural infrastructure. The result of this study indicate that the village fund program has a role in the addition of rural physical facilities and infrastructure. From the analysis results indicate that 40% of the community expressly agree the addition of rural physical facilities and infrastructure. Furthermore, there is an increase in real incomes by the community and it is recognized as much as 69% of rural communities so that the impact of the utilization of village funds for the development of economic desaan has gone well whose benefits can be felt directly by the surrounding community.